2002
DOI: 10.1002/ajmg.10118
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of dopamine D2 receptor polymorphism with bipolar affective disorder in a European multicenter association study of affective disorders

Abstract: Convincing evidence for a genetic component in the etiology of affective disorders (AD), including bipolar affective disorder (BPAD) and unipolar affective disorder (UPAD), is supported by traditional and molecular genetic studies. Most arguments lead to the complex inheritance hypothesis, suggesting that the mode of inheritance is probably not Mendelian but most likely oligogenic (or polygenic) and that the contribution of genes could be moderate or weak. The purpose of the present European multicenter study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…However, given the implication of the D 2 receptor in reward and addiction, one would have to clearly separate antidepressant activity from the risk for potential abuse (Caine et al, 1997;Haddad, 1999;Ellinwood et al, 2002;Rouge-Pont et al, 2002;Farvolden et al, 2003). Furthermore, activation of dopamine function and/or supersensitivity of dopaminergic neurotransmission may play an important role in the induction of mania episodes in patients with bipolar disorders (D'Aquila et al, 2003), another obstacle for the use of D 2 receptor agonists for the treatment of depression (Massat et al, 2002;Yatham, 2002;Serretti et al, 2004). Mood changes observed in bipolar patients from mania to depression are critical events in the course of the disorder and might depend upon parallel changes in mesolimbic dopamine system sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the implication of the D 2 receptor in reward and addiction, one would have to clearly separate antidepressant activity from the risk for potential abuse (Caine et al, 1997;Haddad, 1999;Ellinwood et al, 2002;Rouge-Pont et al, 2002;Farvolden et al, 2003). Furthermore, activation of dopamine function and/or supersensitivity of dopaminergic neurotransmission may play an important role in the induction of mania episodes in patients with bipolar disorders (D'Aquila et al, 2003), another obstacle for the use of D 2 receptor agonists for the treatment of depression (Massat et al, 2002;Yatham, 2002;Serretti et al, 2004). Mood changes observed in bipolar patients from mania to depression are critical events in the course of the disorder and might depend upon parallel changes in mesolimbic dopamine system sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…(Continued ) [Ogden et al, 2004] 9q21.33 BP [Segurado et al, 2003] CP VPA (I) [Ogden et al, 2004] 5q31.3 MDD [Zubenko et al, 2003] (I) BP [Matigian et al, 2007] 5.5 [Li et al, 1999;Massat et al, 2002] (I) BP [Ryan et al, 2006] (D) MDD [Torrey et al, 2005] 5.0 BP [Craddock et al, 1995;Peroutka et al, 1998; [Camp et al, 2005] (I) BP [Middleton et al, 2005] 5.0 (Continued ) [Benes, 2007] 5.0…”
Section: 05e-04mentioning
confidence: 99%
“…This reaction is sensitive to tricyclic antidepressants and electroconvulsive shock therapy (ECST), but not to anxiolytic or major GABA plasma levels kin 40% of depressed, manic, and euthymic mood disorder patients 98,[116][117][118][119][120] 2 in depressed patients 132 GABA enzyme activities kplatelet GABA-T and plasma GAD activities in unipolar and bipolar patients 127,128 Post-mortem studies kGAD activity 130 and mGABA A receptors 141 in the brain of depressed patients k GABA cortical levels with m depression severity in mood disorder patients 151 kexpression of GAD 65 and GAD 67 in prefrontal cortex 148 [141][142][143][144][145][146] Neuroimaging studies kGABA A receptors in the sensory motor cortex of mood disorder patients with akinetic catatonia 152 kGABA occipital cortex levels in depressed patients 153 Neuroendocrine studies (GH response to baclofen ) k in depressed patients 163,164 m in manic patients 161 2 in depressed patients, 162,165,166 Genetic studies Bipolar disorder: association with GABA A receptor a5 (GABRA5) 178 and a3 subunits (GABRA3) 180 possible linkage of GABRA5 and GABA A receptor b1 subunit (GABRB1) loci 181 no association with GABRA1, 179,181,186,188 70,71 Reduced GABA levels in rat nucleus accumbens, brain stem, and cortex have been reported after a session of forced swimming test. 72 Also, muscimol, a GABA agonist, reduced the immobility,...…”
Section: Gaba and The Pathophysiology Of Mood Disordersmentioning
confidence: 99%
“…GABA A receptor a5 subunit (GABRA5) gene distribution has been found to be significantly different in unipolar 177 and bipolar patients 178 compared to healthy controls. Findings from a recent controlled multicenter study showed a significant association between GABA A receptor a1 subunit (GABRA1), but not GABRA5, and unipolar patients 179 and between GABA A receptor a3 subunit (GABRA3), but not GABRA1 and GABRA5, and bipolar patients, 180 suggesting that different GABA A receptor subunits may confer susceptibility to unipolar and bipolar disorders. A linkage study examining two large families segregating bipolar disorder could not exclude linkage of GABRA5 and GABA A receptor b1 subunit (GABRB1) loci in one of the families, although negative results were reported in the other study.…”
Section: 157mentioning
confidence: 99%
See 1 more Smart Citation